The Relationship between Data Privacy and Consumer Trust - Luo Yijia (SHS Web of Conferences, 2025)
Customer trust functions directly as a direct function of their privacy rights. Anxiety about data handling by collectors leads customers to lose trust which might reduce their business involvement. For increasing customer trust businesses should establish proactive precautions to protect their data by providing clear collection policies and strong security protocols. These security practices help build consumer trust which generates better transaction willingness and business accomplishments. Under the Personal Information Protection Law of the People’s Republic of China together with the Civil Code of the People’s Republic of China businesses must satisfy legal requirements during consumer data management. The absence of proper data protection measures can lead to major penalties under the law. Improving consumer trust in data security requires companies to implement common industry standards that include getting users’ clear permissions and providing updated privacy policies and limiting data utilization to predefined purposes. Companies need to develop quick response systems which will notify affected users and regulatory bodies about breaches while also needing to develop mechanisms to address data security incidents promptly. Third-party audits through independent bodies provide more assurance about compliance.